The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1136/gut.2010.215665
|View full text |Cite
|
Sign up to set email alerts
|

Composition and energy harvesting capacity of the gut microbiota: relationship to diet, obesity and time in mouse models

Abstract: The relationship between the microbial composition and energy harvesting capacity is more complex than previously considered. While compositional changes in the faecal microbiota were confirmed, this was primarily a feature of high-fat feeding rather than genetically induced obesity. In addition, changes in the proportions of the major phyla were unrelated to markers of energy harvest which changed over time. The possibility of microbial adaptation to diet and time should be considered in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
508
8
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(598 citation statements)
references
References 49 publications
49
508
8
10
Order By: Relevance
“…Interestingly, they also reported an increase in Fiaf levels in the obese mice, contradicting the mechanistic fi ndings described previously ( 5 ). Using an ob / ob mouse model fed low-fat and high-fat diets and compared with wild-type mice, Murphy et al ( 21 ) found an increased Firmicutes / Bacteroidetes ratio as previously described, but determined that the compositional changes were primarily the result of the high-fat diet rather than genetic obesity. Finally, results obtained from a mouse model with a humanized gut microbiome indicate that the gut microbes undergo a rapid shift in only a single day aft er switching from a low-fat, plant polysaccharide -rich diet to a high-fat, high-sugar, " Western " diet ( 22 ).…”
Section: © 2012 By the American College Of Gastroenterologycontrasting
confidence: 52%
“…Interestingly, they also reported an increase in Fiaf levels in the obese mice, contradicting the mechanistic fi ndings described previously ( 5 ). Using an ob / ob mouse model fed low-fat and high-fat diets and compared with wild-type mice, Murphy et al ( 21 ) found an increased Firmicutes / Bacteroidetes ratio as previously described, but determined that the compositional changes were primarily the result of the high-fat diet rather than genetic obesity. Finally, results obtained from a mouse model with a humanized gut microbiome indicate that the gut microbes undergo a rapid shift in only a single day aft er switching from a low-fat, plant polysaccharide -rich diet to a high-fat, high-sugar, " Western " diet ( 22 ).…”
Section: © 2012 By the American College Of Gastroenterologycontrasting
confidence: 52%
“…The intake of HFD has been shown to negatively alter the gut microbiota [50]. Gut dysbiosis has been linked with endotoxin-mediated chronic disease in mouse models [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that obese people have an increased abundance of Firmicutes in the gut microbiota compared with lean people (8,9). The mouse gut microbiota is also responsive to increased energy intake, with an increased abundance of Firmicutes and reduced abundance of Bacteroidetes (10)(11)(12). In addition, a number of research groups have reported that the supplementation with prebiotics and/or probiotics tends to increase the abundance of Bifidobacterium in humans and animals (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Total bacterial cell numbers in 1 g of human feces is estimated at ~10 11 -10 12 , and the dominant bacterial phyla of the human gut microbiota are the Firmicutes, Bacteroidetes, and Actinobacteria with a lower relative abundance of Verrucomicrobia and Proteobacteria (1,2). The composition of gut microbiota has been shown to vary with clinical conditions such as type 2 diabetes, inflammatory bowel disease, nonalcoholic fatty disease, and allergy (3)(4)(5)(6).…”
mentioning
confidence: 99%